The income tax - Noble, O.E. (My University, 1897)
Introduction: In this economic and bread seeking age, it seems to me that the greatest question that could come before a democratic people, is their method of taxation. Our present taxes are unjust from their very principles; the Income Tax is objectionable principally because the people have not been cultivated to such a system. Then what remains for us to do? It remains for us to teach the masses that there can be no justice in taxation and hence no progress in social development, until the government knows the amount of revenue each person enjoys. Then again the greatest draw back today against any advance in Political Economy is the lack of proper statistics, because the people do not keep an account of their business. Hence the government runs its business in the same careless and loose way. Probably the greatest work of the twentieth century will be the establishment of the system of the Income Tax.
Citation: Noble, O.E. The income tax. Senior thesis, Kansas State Agricultural College, 1897.
Morse Department of Special Collections
Keywords: History; Income tax; Theses; Manuscripts (documents)